1998
DOI: 10.1183/09031936.98.12010082
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiolitis obliterans syndrome in lung transplant recipients is associated with increased neutrophil activity and decreased antioxidant status in the lung

Abstract: Long-term survival of lung transplant recipients is limited by the advent of obliterative bronchiolitis and irreversible airways obstruction, e.g. bronchiolitis obliterans syndrome (BOS). This study investigated whether inflammatory cells and their activation markers were increased in bronchoalveolar lavage (BAL) and transbronchial biopsies (TBB) from patients with BOS. Levels of antioxidants in BAL fluid were also assessed. BAL fluid and TBB from six single-lung, two bilateral-lung, and five heart-lung transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
74
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 16 publications
6
74
1
1
Order By: Relevance
“…DIGIOVINE et al [10] performed chemotactic studies in which IL-8 appeared to account for the neutrophil presence, and IL-8 was also found in the peribronchial region of their transbronchial biopsy specimens. Furthermore, in a cross-sectional study evidence was recently found of neutrophil granulocyte activation in the form of increased BAL fluid levels and degree of immunohistochemical staining of MPO in TBBs from BOS patients compared to matching controls [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DIGIOVINE et al [10] performed chemotactic studies in which IL-8 appeared to account for the neutrophil presence, and IL-8 was also found in the peribronchial region of their transbronchial biopsy specimens. Furthermore, in a cross-sectional study evidence was recently found of neutrophil granulocyte activation in the form of increased BAL fluid levels and degree of immunohistochemical staining of MPO in TBBs from BOS patients compared to matching controls [9].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, patients with manifest BOS proved to have significantly increased levels of both IL-8 and MPO, as well as neutrophil percentages, in BAL fluid compared to matched controls without BOS [9]. Furthermore, DIGIOVINE et al [10] reported from neutrophil chemotaxis experiments that IL-8 accounted for a significant amount of the neutrophil chemotactic activity found in lung transplant recipients with BOS.…”
mentioning
confidence: 97%
“…Other pro-inflammatory cytokines, such as IL-8, TNF-a and IL-1b, are also highly expressed in BO patients [127,148,165]. This inflammatory environment could contribute to EMT in BO.…”
Section: Emt and Bo Following Lung Transplantationmentioning
confidence: 99%
“…Studies in the inflammatory environment of BO have shown that TGF-b is one of the most important factors involved in the fibrotic process and high levels of TGF-b are found in the BAL from BO patients [148,[161][162][163][164][165]. Other pro-inflammatory cytokines, such as IL-8, TNF-a and IL-1b, are also highly expressed in BO patients [127,148,165].…”
Section: Emt and Bo Following Lung Transplantationmentioning
confidence: 99%
See 1 more Smart Citation